Qur'an Learning Strategies In Batee Shok Village, Sabang City: (Comparative Study Of Tpa Al-Ikhlas And Meunasah Nurul Badri) - Irmayani, Irmayani; Zulfatmi, Zulfatmi; Hayati, Hayati (Teunuleh Publisher, 2025)
This study aims to analyze and compare the Quran learning strategies for children in Gampong Batee Shok, Sabang City, focusing on two Quranic institutions: TPA Al-Ikhlas and Meunasah Nurul Badri. The research uses a qualitative approach with a comparative study design. Data were collected through interviews, observations, documentation, and tests conducted at both institutions. Data analysis was carried out using a comparative descriptive analysis technique to identify the differences and similarities in the learning strategies applied at each location. The results of the study show that the Quran learning strategies at TPA Al-Ikhlas and Meunasah Nurul Badri in Gampong Batee Shok, Sabang City, are comprehensive despite the differences. TPA Al-Ikhlas uses the Ummi curriculum with a focus on Tajwid, reading fluency, and gradual understanding of verses, along with rewarding students to motivate them. Meunasah Nurul Badri combines the Iqra' and Mujawad techniques with color visualization and congregational prayer practice. Both institutions have motivational programs in the form of competitions and awards, as well as a focus on teacher training. TPA Al-Ikhlas faces challenges related to attendance and parental involvement, while Meunasah Nurul Badri struggles with limited facilities and teachers. The teaching approaches at both institutions are diverse, with TPA Al-Ikhlas emphasizing a fun and structured learning environment, while Meunasah is more creative and flexible. The evaluation at TPA Al-Ikhlas is more structured with weekly and monthly exams, whereas Meunasah follows a more flexible bi-weekly evaluation with better results at Meunasah. Both institutions involve parents in the evaluation process to monitor the students' progress.